Meta-Analysis the Effect of Section Caesarea on Early Breastfeeding Initiation - Nurkholifa, Ferda Fibi Tyas; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Journal of Maternal and Child Health, 2021)
Background: Early Initiation of Breastfeeding is the baby's first activity to find the mother's nipple within the first hour of birth. UNICEF and WHO recommend Early Breastfeeding Initiation as a strategy to achieve the 4th MDG, namely reducing child mortality. Early Breast